Collage women of the Prix Pictet since 2008 - Benson, Michael 1962-; Mann, Sally 1951-; Dalley, Jan (gestalten, 2022)
Collage showcases the recent work on the theme of sustainability of 64 outstanding female presenting photographers who have been shortlisted or nominated for the Prix Pictet, the leading global award in photography and sustainability. Their strong and poetic images address the most urgent environmental and social problems facing the planet today. The Prix Pictet is the leading global award in photography and sustainability. Founded in 2008 to draw worldwide attention and stimulate action on issues of sustainability through the medium of photography, the award is supported by the leading asset and wealth management firm, Pictet Group
Keywords: Geschichte 2008-2022; Prix Pictet; Collage; Fotografin; Fotografie; Bildband